Technological Checklist for Kidney and Liver Transplantation in a Multidisciplinary Hospital. Clinical Protocol - B. I. Yaremin; S. Yu. Pushkin; A. S. Navasardyan; B. I. Kazymov; E. Yu. Anosova (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
This clinical protocol delineates the technological requirements for performing kidney and liver transplantation procedures in a multidisciplinary hospital setting. The protocol has been developed based on clinical guidelines from leading international societies and has been approved by the Samara Regional Branch of the Interregional Public Organization "Society of Transplantologists" (Protocol No. 11 dated July 1, 2024). It is recommended for use in assessing a hospital's readiness to implement transplantation programs. The technologies specified in the protocol may be implemented either through the hospital's own resources or via agreements with other healthcare institutions or through outsourcing arrangements.